The Peculiarities of the II-IV Form Pupil’s Humanity Maturity - Bakutytė, Rima (Acta Paedagogica Vilnensia, 1998)
This article presents the scientific research results: some peculiarities of primary school pupils’ humanistic upbringing in sex and age facets. The data shows that primary school children’s humanistic behaviour is not sufficiently stable in relationship with their friends. Girl’s humanistic behaviour is more stable than boy’s. The level of moral knowledge is not sufficient too.